Football and Nation Building in Colombia (2010-2018) The Only Thing That Unites Us - Watson, Peter J. (Liverpool University Press, 2022)
This book explores the pivotal role that football played as part of Colombian President Juan Manuel Santos' national unity project centred on the peace process with the FARC. Football has huge political and social capital in Latin America, and has often been rhetorically deployed by governments for various ends; rarely, however, has football's power and potential been used in such a deliberate, strategic and active way towards a national peace process and targeted such enduring divisions that have historically impeded a sense of a united nation and national identity. Football in Colombia is understood popularly as one of the few things capable of uniting the country, a belief that Santos seized upon as the national team had a successful campaign in the 2014 World Cup. This first book on Colombian football in English explores previous iterations of football nationalism in the country, including the El Dorado and 'Narcofootball' eras, before analysing Santos' three-pronged strategy empowering professional and amateur football, including the use of political speeches and Twitter, legislation and public policy, and Sport for Development and Peace campaigns, with a particular focus on football in the FARC demobilisation and reincorporation camps following the historic peace agreement.